REGULATORY RECONSTRUCTION OF E-COMMERCE TRANSACTIONS IN PERSPECTIVE LEGAL PROTECTION FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN INDONESIA - Raendhi Rahmadi; Ahmad Fajar Herlan; Beggy Tamara (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
This study, answer the basic problem about 1th. Standard of legal protection for micro, small and medium enterprises in the implementation of E-Commerce to create social and economic justice for all Indonesian people, and 2nd. The government it???s can create social and economic justice for all Indonesians, especially for micro, small and medium entrepreneurs who run e-commerce in Indonesia. Why we need to make the description from this problem is because we all know that real business in micro economical is fundamental from the growth of economical of the country. So, we have to collect some of the problems from the public based on the experience of the business community, and trying to answer the problem with better solutions. This study aims to find out the Regulatory Reconstruction of E-Commerce Transactions In Perspective Legal Protection For Micro, Small and Medium Enterprises In Indonesia. This descriptive-analytic study applied the experience of the business community approach. Meanwhile, the type of study itself was normative juridical. Secondary legal material both in the form of regulations and legal theories were used in this study, even though it still includes economic and social values in it. The regulations on Micro, Small And Medium Enterprises used were Law No 20 of 2008, Law No. 11 of 2008 on Electronic Information and Transactions, Government Regulation on The Implementation of Law No 20 of 2008 on The regulations on Micro, Small And Medium Enterprises No. 17 of 2013, and Government Regulation on Trading via electronic systems No.80 of 2019. The results show that both regulations correspond to each other, however, it is necessary to regulate other needs related to protection in implementation such as protection of local entrepreneurs, this is a more specific matter such as imposing certification on the implementation of electronic transactions to Micro, Small And Medium Enterprises players, to maintain trust from the market.